Why Do Non‐Resident Citizens Get Elected? Candidates' Electoral Success in Ecuadorian Extraterritorial Districts - Umpierrez de Reguero, Sebastián (2024)
To the growing literature on non-resident citizens’ special representation, we contribute with a systematic examination of the role of descriptive representation of citizens living abroad in elections for extraterritorial districts. Using data for the 308 candidacy observations in three two-seat extraterritorial districts in five legislative elections held between 2007 and 2021 in Ecuador, for a total of 30 seats, we test four hypotheses related to the electoral rules, party-level, and socio-demographic factors of non-resident candidates. Ecuadorian non-resident candidates benefit from their incumbency position and party affiliation, along with left-wing ideological ascription and belonging to party organizations that pushed for voting rights abroad and that manifest an interest in emigrant issues. This article contributes to showing what gets emigrants elected in extraterritorial seats and offers a within-country comparison connecting elections with legislative politics across national borders.